Arthroscopic treatment for posteromedial talar process fracture (Cedell fracture): a case report - Fernandes Martins, Carla; Nunes Gomes, Patrícia Alexandra; Reino dos Santos Felicíssimo, Paulo Jorge (Journal of the Foot & Ankle, 2021)
Fracture of the posteromedial talar process (Cedell fracture) is a rare injury and is easily misdiagnosed as a simple ankle sprain. Suspicion should be heightened if specific mechanisms of injury are present, and, in these cases, a CT scan should be performed. Significant ankle pain and disability can result if these injuries are not identified and treated properly. Few cases have been described in the literature, and the efficacy of surgical techniques and approaches for fractures of the posterior talar process remains controversial. We report a 56-year-old man with an acute posteromedial talar fracture treated arthroscopically. This approach provides good access to the posterior ankle compartment, subtalar joint, and extraarticular structures, which may allow fracture reduction and fixation under arthroscopic visualization. Level of Evidence V; Therapeutic Studies; Expert Opinion.